Book Review: Religion Crossing Boundaries: Transnational Religious and Social Dynamics in Africa and the New African Diaspora - Akanmu Adebayo (Journal of Global Initiatives, 2011)
Review of Religion Crossing Boundaries: Transnational Religious and Social Dynamics in Africa and the New African Diaspora, by James Spickard and Afe Adogame. (2010). Leiden: E.J. Brill; ISBN-I0: 90-04-18730-8